2010
DOI: 10.1111/j.2042-3306.2010.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweat composition in Arabian horses performing endurance exercise on forage‐based, low Na rations

Abstract: SummaryReasons for performing study: Excessive sweat loss during endurance exercise may lead to electrolyte disturbances and previous research suggests dietary factors may affect hydration status. While investigating the effect of dietary fibre type on hydration status, sweat samples were collected which allowed for the evaluation of sweat composition in horses consuming forage-based, low sodium (Na) rations. Objective: To investigate sweat composition in Arabian horses performing endurance type exercise while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Breed or even individual differences may also play a role. Spooner et al [18] observed a comparatively low sodium content in the sweat of Arabian horses. Evaporation of water during sweat collection may lead to an overestimate of the electrolyte content of sweat [5].…”
Section: Introductionmentioning
confidence: 99%
“…Breed or even individual differences may also play a role. Spooner et al [18] observed a comparatively low sodium content in the sweat of Arabian horses. Evaporation of water during sweat collection may lead to an overestimate of the electrolyte content of sweat [5].…”
Section: Introductionmentioning
confidence: 99%
“…2010). Another study documented unusually low sweat sodium concentrations during exercise in horses consuming 3 different forage rations providing sodium at only 6.6% of National Research Council (NRC) recommendation (Spooner et al . 2010).…”
Section: Nutrition Of the Exercised Horsementioning
confidence: 99%
“…In horses, loss of Na via sweat plays an important role in their Na metabolism because they rely on sweating as major mechanism for heat dissipation during exercise (Coenen, 2005; Cohen et al, 1993; McCutcheon & Geor, 2014; Meyer et al, 1990). Horse sweat is hypertonic in relation to the plasma and contains considerable amounts of Na, ranging between 2.0 and 5.7 g/L (reviewed by Spooner et al, 2010). However, the sweat glands do not conserve Na, regardless of the horse's body stores (Lindner et al, 1983; Spooner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Horse sweat is hypertonic in relation to the plasma and contains considerable amounts of Na, ranging between 2.0 and 5.7 g/L (reviewed by Spooner et al, 2010). However, the sweat glands do not conserve Na, regardless of the horse's body stores (Lindner et al, 1983; Spooner et al, 2010). Sweat losses of around 1 L/100 kg body weight (BW) per hour during light exercise under temperate conditions (in Welsh ponies and crossbreeds, Meyer et al, 1990) may increase to 2–2.5 L/100 kg BW per hour when exercised in hot, humid conditions (NRC, 2007), thus leading to excessive Na losses.…”
Section: Introductionmentioning
confidence: 99%